Revisiting the concept of bout: associations of moderate-to-vigorous physical activity sessions and non-sessions with mortality - Tongyu Ma; John Sirard; Lin Yang; Ye Li; Sharon Tsang; Amy Fu (BMC, 2024)
Abstract Introduction Current physical activity guidelines recommend 150 min of moderate-to-vigorous physical activity (MVPA) for health benefits, regardless of the pattern of MVPA. However, MVPA that occurs in sessions (MVPA-S) may have different health implications compared to MVPA that is not accumulated in sessions (MVPA-nonS). This study aimed to investigate the associations of MVPA-S and MVPA-nonS with mortality. Methods We conducted a cohort study of the National Health and Nutrition Examination Survey 2003-2006 (n = 5,658) with accelerometer-measured physical activity at baseline and mortality followed through December 31, 2019. A session was defined as a time window of 30 min or longer where the average intensity was at or above 2020 counts/minute. MVPA accumulated within such sessions was quantified as MVPA-S, while MVPA accumulated outside the sessions was quantified as MVPA-nonS. We examined the joint association of MVPA-S and MVPA-nonS by classifying the participants into four groups (both < 75 min/week [referent], MVPA-S ≥ 75 and MVPA-nonS < 75, MVPA-S < 75 and MVPA-nonS ≥ 75, and both ≥ 75). We used 75 min as the cut-point because it is half of the guideline-recommended MVPA volume where a strong MVPA-mortality association has been observed in previous studies, and because it was close to the median of MVPA-nonS (75 min/week was the 54th percentile), allowing a sufficient sample size in each group for testing statistical significance. The hazard ratios and 95% confidence intervals were estimated with adjustment for important confounders. Results During 13.9 years of follow-up (74,988 person-years), there were 1,424 deaths, out of which 472 were related to cardiovascular diseases (CVD). Compared to the referent combination (both < 75), the hazard ratios in the other three combinations were 0.48 (0.33-0.69), 0.85 (0.71-1.01), and 0.45 (0.30-0.67) for all-cause mortality; and were 0.34 (0.17-0.70), 0.96 (0.69-1.33), and 0.40 (0.17-0.90) for CVD mortality, respectively. Results were largely consistent in the spline-based models, age- and sex-stratified analyses, complete-case analysis, competing risk analysis, and the analysis excluding deaths within two years of follow-up. Conclusion In conclusion, MVPA accumulated in sessions that lasted at least 30 min was associated with significant reductions in all-cause and CVD-specific mortality risks. The health implications of MVPA that were not accumulated in such sessions warrant further investigation.